Prediction Model Based on Transfer Characteristics of Heavy Metals from Soils to Yam Tubers Grown in Wukari Farmland - Achimugu, Augustina; Wansah, John F.; Emmanuel, Onuh G.; John, Jeremiah J.; Bawa-Boyi, Emmanuel U. (African Journal of Biochemistry and Molecular Biology Research, 2024)
Heavy metal contamination in agricultural soils poses a significant threat to human health because these elements accumulate in food crops. The study's aim was to make a prediction model based on the soil's properties that would show how well yam tubers would take up six heavy metals (Pb, Cd, Cr, Cu, Ni, and Zn) in Wukari farmland soils. Soil and plant samples were collected from different locations within Wukari, and the physiochemical properties of the soils, along with the concentration of heavy metals, were determined. For the yam tubers, the samples were peeled, washed, dried, pulverized, and then analyzed for heavy metals with the atomic absorption spectrophotometer (AAS). Step-wise linear regression analysis was employed to develop a prediction model to estimate the potential uptake of heavy metals by yam tubers based on the soil properties. The results showed that the farmland sample soils are sandy loamy and slightly alkaline, with a mean pH of about 7.88. The prediction model demonstrated good performance in predicting the uptake of all six heavy metals, with R2 ranging from 0.683 (Pb) to 0.998 (Zn) in the fitted empirical model. This work's findings will provide other researchers with a cost-effective tool for assessing potential contamination based on readily available soil data.